High prevalence of Schistosoma mansoni in six health areas of - Kasansa health zone, Democratic Republic of the Congo: short report. - Sylvie Linsuke; Sabin Nundu; Sylvain Mupoyi; Rodin Mukele; Faustin Mukunda; Madeleine Mbuyi Kabongo; Raquel Inocêncio da Luz; Jean-Pierre Van Geertruyden; Marc Van Sprundel; Marleen Boelaert; Katja Polman; Pascal Lutumba (Public Library of Science (PLoS), 2014)
School-aged children suffer the most from schistosomiasis infection in sub Saharan Africa due to poverty and limited sanitary conditions. Mapping of disease burden is recommended and there is a need of updating prevalence data which is as old as 20 years in the Democratic Republic of Congo. An epidemiological and parasitological study was carried out in 2011 in the health zone of Kasansa. Six health areas (HA) were included in the study. In each health area, one primary school was selected. School-aged children were screened for S. mansoni infection using parallel Kato-Katz and direct microscopy techniques. A total of 335 school-aged children were screened. The average prevalence was 82.7% and ranged between 59.5-94.9%. Four of the six HAs had a prevalence level over 91%. Of all infected children, about half 112 (43.2%) had light parasite density. These results demonstrate that Schistosoma mansoni infection is a bigger problem than anticipated and there is an urgent need to implement effective control measures.